A Single Bout of Aerobic Exercise Impact to Consolidation of Bilateral Movements in Older Adults - Florinta Čičirkaitė; Rima Solianik (Reabilitacijos Mokslai: Slauga, Kineziterapija, Ergoterapija)
Background. Aging is associated with a decline in motor coordination and learning efficiency. A single bout of exercise is used to improve learning of unilateral movements in older adults; however, the effect on learning of bilateral movements remains unclear.